Pengaruh Permainan Kartu Angka Bergambar terhadap Kemampuan Mengenal Angka 1-10 pada Anak Usia 4-5 Tahun di TK Dharma Wanita Persatuan Pandanan - Masullah Aprilia; Aisyah, Aisyah (CV. ULIL ALBAB CORP, 2025)
The study aims to determine the effect of the application of picture number card games on the ability to recognize the numbers 1-10 in children aged 4-5 years at Dharma Wanita Persatuan Pananan Kindergarten. Early childhood is a period of children's cognitive development, knowing numbers. Picture number card games are believed to improve children's understanding of number concepts by being interactive. This research is quantitative with a One Group Pretest and Posttest design, data collection through observation, documentation, and tests. A sample of 17 children was selected for non-random sampling. The analysis using the t-test found out the difference between pre-test and post-test results. Research shows that the application of picture number card games has an effect on the ability to recognize the numbers 1-10 in children aged 4-5 years, the significance value of < 0.001 means less than 0.05. Children who participated in the learning of pictorial number card media significantly improved in recognizing the shape of numbers, sorting numbers, and relating numbers to the number of objects. Picture number card games are effective in improving children's numeracy skills. This study provides suggestions for teachers, educational institutions, and parents to support the use of this media to recognize children's numbers.